SKOVORODA ON THE ROLE OF MENTAL EDUCATION IN PERSONALITY FORMATION - Друганова, О.; Білик, В. (New Collegium, 2020)
The article analyzes the creative heritage of G. Skovoroda. The views of the thinker on the problems of mental education, its importance in the formation of personality were revealed. The attitude of the teacher to the native language and other languages, folk traditions, their impact on the development of the child was determined. The philosopher’s proposals on changing the content of instruction and recommendations on cognition of the world and oneself in it were voiced. G. Skovoroda’s thought about the role of sciences (his- tory, philosophy, literature, music) in the formation of the foundations of mental education was characterized. The methods of training and education that are most conducive to the development of mental inclinations were highlighted. The authors revealed the connection between the philosophical foundations of the scientist's worldview and his views on the principles, teaching methods.